On the location of Atlantis - Fedchenko Oleg Dmitrievich (Studia Humanitatis)
The paper examines the localization of the Atlantis Island. Based on information from the texts of ancient Greek scientists, the author concludes that Atlantis is the Atlas Ridge and the African-Sicilian threshold that ended up under the waters of the Mediterranean Sea. It is this geographical object that meets all the features noted by ancient authors.